Assessing the Pragmatic Competence of English Language Learners: A case study approach (Journal of Advances and Scholarly Researches in Allied Education, 2024)
While good pragmatic competence is essential for all language users, it is often significantly neglected in the context of English language learners (ELLs). To be able to utilise language successfully in a variety of social and cultural contexts, it is necessary to have an understanding of speech acts, ways of politeness, and hidden meanings. In this research, a case study approach is used to assess the pragmatic ability of English Language Learners (ELLs) by analysing their spoken and written interactions in real-world situations. According to the findings of the study, some of the most significant challenges are the transfer of pragmatics from native languages, sociocultural misunderstandings, and the challenge of conforming to the norms of English-speaking societies. Discourse analysis, interviews, and observations were some of the qualitative methods that were used in the process of identification of these difficulties. According to the findings, a significant number of pupils may have trouble being indirect, adhering to principles of civility, and understanding when it is appropriate to engage in appropriate behaviour. It's possible that this may lead to misunderstandings and accidental rudeness. The findings of this study give more evidence that traditional language programs put a greater emphasis on grammatical accuracy than they do on the students' capacity to communicate successfully.